1997
DOI: 10.33584/jnzg.1997.59.2236
|View full text |Cite
|
Sign up to set email alerts
|

Tall fescue use on dairy farms

Abstract: Tall fescue (Festuca arundinacea Schreb.) is now well proven on New Zealand dairy farms as a pasture species capable of producing high levels of milk production. Compared with perennial ryegrass (Lolium perenne) it offers benefits of higher annual and summer growth, higher clover contents in pasture, higher green leaf to stem ratios in summer, reduced plant pulling, better animal health, grass grub (Costelytra zealandica) and Argentine stem weevil (Listronotus bonariensis) tolerance, tolerance of wet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The tall fescue used was a summer active Continental cultivar, Advance, infected with the novel endophyte strain MaxP™. Advance was chosen for its establishment vigour, seasonal and annual production, and persistence (Fraser & Lyons, ; Milne, Shaw, Powell, Pirie, & Pirie, ). All grass seed was Superstrike ® ‐treated.…”
Section: Methodsmentioning
confidence: 99%
“…The tall fescue used was a summer active Continental cultivar, Advance, infected with the novel endophyte strain MaxP™. Advance was chosen for its establishment vigour, seasonal and annual production, and persistence (Fraser & Lyons, ; Milne, Shaw, Powell, Pirie, & Pirie, ). All grass seed was Superstrike ® ‐treated.…”
Section: Methodsmentioning
confidence: 99%
“…Tall fescue is grown to increase summer forage production. The importance of tall fescue in New Zealand pastoral farming has been widely discussed, along with drawbacks (Brock 1983;Easton et al 1994;Milne et al 1997). Reported problems include establishment, fertility, grazing management requirements and persistence (Easton et al 1994).…”
Section: Tall Fescuementioning
confidence: 99%
“…McCallum et al (1992) and Thomson et al (1988) showed that tall fescue produced higher annual DM yields than ryegrass without irrigation; and under cutting, Martin (2008) showed that irrigated tall fescue had higher water use efficiency and produced more DM than ryegrass. However, the slow establishment and management difficulties of tall fescue (Easton et al 1994) have limited its use on dairy farms (Milne et al 1997). The recent development of cultivars bred for improved establishment (Fraser & Lyons 1994) with the inclusion of a non-toxic novel endophyte, MaxP ® , which protects against a wide range of pasture pests, has renewed interest in this forage.…”
Section: Introductionmentioning
confidence: 99%